How Are Neonatology Fellows Trained for Antenatal Periviability Counseling? - Feltman, Dalia M.; Williams, David D.; Carter, Brian S. (American Journal of Perinatology, 2017)
Background Studies have shown rates of life-sustaining treatments for periviable newborns vary by center, centers' differing periviability approaches affect trainees' views, and formal communication training for neonatology fellows is uncommon. Parents of imperiled newborns report unmet emotional and spiritual needs. This study sought to understand how fellows learn to support parents and their periviable newborns through exposure to institutional clinical approaches and by formal curriculum.Methods All the U.S. neonatology fellowship program directors were invited to complete an online anonymous survey. Data were analyzed with descriptive statistics.Results In this study, 56 of 98 directors (57%) responded. Training centers differed in delivery room options offered and recommended for periviable newborns. Providing parents written information and neonatology and obstetrics co-counseling were uncommon. Directors reported weaknesses in training fellows to support parents' spiritual and emotional needs, and < 50% reported formal policies for involving social workers or chaplain. Fellows learned periviability counseling in 95% programs by observing attending physicians; however, only 54% directors reported typical joint daytime counseling with fellows and attending physicians.Conclusion Training programs exposed fellows to different periviability care approaches, identified weaknesses in teaching support provision for parents' needs, and appeared to miss opportunities for clinical modeling of counseling and comfort care provision.
Keywords: ethics; periviable; antenatal counseling; decision making; resuscitation; neonatology; education